LOCAL MINOR TUBERS IN YOGYAKARTA SPECIAL REGION, PHYSICOCHEMICAL PROPERTIES AND DIVERSIFIED PROCESSING - Yeyen Prestyaning Wanita (Fakultas Pertanian, Universitas Janabadra, 2018)
Yogyakarta Special Region has many potential tubers, both major tuber (cassava and sweet potato) and minor tuber (taro, ‘gadung’, arrowroot, ‘ganyong’, and other type of minor tubers. The development of utilization of minor tubers is left behind when compared to the mayor tubers. Though the minor tuber, have a variety of diversity abundant, with physicochemical content, especially carbohydrates that are not inferior to the major tubers, so it is potentially developed and used as local food, substitute for rice and flour. The minor tubers are potentially exploited as composite starch, starch, and as industrial raw materials. The dissemination of information on minor tuber processing improvements, and the diversification of its processing, can improve community knowledge. So that in the end, it can increase the bulb storage period, increase the use value and tuber economy, and increase the income and welfare of the family, and encourage the robustness of people's food security.